3-pass and 5-pass laser grooving & die strength characterization for reinforced internal low-k 55nm node wafer structure via heat-treatment process - Mohammad Nazri M.H.; Yong T.C.; Yusof F.B.; Soon How Thien G.; Yoong C.K.; Kar Y.B. (Emerald Publishing, 2025)
Purpose: Die edge quality with its corresponding die strength are two important factors for excellent dicing quality especially for low-k wafers due to their weak mechanical properties and fragile structures. It is shown in past literatures that laser dicing or grooving does yield good dicing quality with the elimination of die mechanical properties. This is due to the excess heat energy that the die absorbs throughout the procedure. Within the internal structure, the mechanical properties of low-k wafers can be further enhanced by modification of the material. The purpose of this paper is to strengthen the mechanical properties of wafers through the heat-treatment process. Design/methodology/approach: The methodology of this approach is by heat treating several low-k wafers that are scribed with different laser energy densities with different laser micromachining parameters, i.e. laser power, frequency, feed speed, defocus reading and single/multibeam setup. An Nd:YAG ultraviolet laser diode that is operating at 355 nm wavelength was used in this study. The die responses from each wafer are thoroughly visually inspected to identify any topside chipping and peeling. The laser grooving profile shape and deepest depth are analysed using a laser profiler, while the sidewalls are characterized by scanning electron microscopy (SEM) to detect cracks and voids. The mechanical strength of each wafer types then undergoes three-point bending test, and the performance data is analyzed using Weibull plot. Findings: The result from the experiment shows that the standard wafers are most susceptible to physical defects as compared to the heat-treated wafers. There is improvement for heat-treated wafers in terms of die structural integrity and die strength performance, which revealed a 6% increase in single beam data group for wafers that is processed using high energy density laser output but remains the same for other laser grooving settings. Whereas for multibeam data group, all heat-treated wafer with different laser settings receives a slight increase at 4% in die strength. Originality/value: Heat-treatment process can yield improved mechanical properties for laser grooved low-k wafers and thus provide better product reliability. ? 2024, Emerald Publishing Limited.